Solvent-free synthesis of 2H-indazolo[2,1-b] phthalazine-triones promoted by cavitational phenomenon using iodine as catalyst - Varghese, Anitha; Nizam, Aatika; Kulkarni, Rajani; George, Louis (European Journal of Chemistry, 2013)
An environmentally benign, simple and efficient protocol for the synthesis of 2H-indazolo[2,1-b] phthalazine-triones by condensation of phthalhydrazide, aromatic aldehydes and dimedone under solvent-free ultrasound assisted conditions employing a safe, readily available iodine as catalyst has been described. This process is a valuable addition as it devoids the use of any solvent and takes place in short duration of time giving good yield of the products.